Integrating multiple approaches to learning as a means of promoting quality education for Roma students - Spajić-Vrkaš, Vedrana (Array, 2013)
Drawing from the 2003 World Bank report on Roma in which it is stated that „the roots of Roma poverty and exclusion are multidimensional and interconnected and, thus, need to be addressed from many sides and in a concerted way”, we argue that the multidimensionality of the problem and interconnectedness of its dimensions mean that the approach to solving the problem needs to be multidimensional and inclusive so as to ensure Roma inclusion in the mainstream society while maintaining their cultural and social autonomy. Two key dimensions of the solution are offered. The “What” dimension relates to the formal recognition of the right to equality and the right to difference, respect from the side of the mainstream society, active participation in decision-making, self-representation and just redistribution, while the “Where “ dimension encompasses education, employment, health, housing and culture-based entrepreneurship. The argument is made about the need for developing a culture-sensitive approach to inclusion based on a systemic understanding of factors affecting the quality of Roma education, including the most salient challenges.